Dynamic HTML : the HTML developer's guide - Rule, Jeff, 1968- (Addison-Wesley, 1999)
If you're tired of programming manuals that start with trivial details and examples and illustrate only the most basic demos, then this book is for you. In Dynamic HTML: The HTML Developer's Guide you will learn DHTML the same way you probably learned HTML--by looking at other people's source code. Because scripting with DHTML is much more complex than with regular HTML, many web developers are hesitant to begin learning this vital technology. Dynamic HTML is a valuable resource to help you master this important new skill. Both a comprehensive reference guide and a clear tutorial, this book explains the principles behind DHTML and, using a learn-by-example approach, enables you to acquire techniques for effective DHTML scripting. Inspired by the author's web-based DHTML Demos, this book contains solid examples of DHTML that can be taken apart and plugged into existing web pages for dynamic effects.